Does abstract thinking facilitate information processing? Evidence from financial analysts - LI, Frank Weikai (Institutional Knowledge at Singapore Management University, 2023)
We study whether abstract thinking – an essential cognitive trait established by psychological and neuroscientific studies – facilitates analysts’ information processing. Exploiting analysts’ questions during earnings calls, we construct an Abstract Thinking Index (ATI) that measures their tendency to involve abstract words, logical reasoning, broader topics, and future outlooks. We find that abstract thinking improves analysts’ forecast accuracy and recommendation informativeness. Consistent with abstract thinking featuring identifying central characteristics and comprehending intangible things, ATI has stronger effects for firms with fundamentals co-moving more with peers and less tangible information. Additional analyses suggest that ATI captures analysts’ cognitive traits rather than information access.